The Java EE 6 tutorial : advanced topics - Jendrock, Eric (Addison-Wesley, 2013)
The Java EE 6 Tutorial: Advanced Topics, Fourth Edition, is a task-oriented, example-driven guide to developing enterprise applications for the Java Platform, Enterprise Edition 6 (Java EE 6). Written by members of the Java EE 6 documentation team at Oracle, this book provides new and intermediate Java programmers with a deep understanding of the platform. This guide-which builds on the concepts introduced in The Java EE 6 Tutorial: Basic Concepts, Fourth Edition-contains advanced material, including detailed introductions to more complex platform features and instructions for using the latest version of the NetBeans IDE and the GlassFish Server, Open Source Edition. This book introduces the Java Message Service (JMS) API and Java EE Interceptors. It also describes advanced features of JavaServer Faces, Servlets, JAX-RS, Enterprise¿ JavaBeans components, the Java Persistence API, Contexts and Dependency Injection for the Java EE Platform, web and enterprise application security, and Bean Validation. The book culminates with three new case studies that illustrate the use of multiple Java EE 6 APIs.